A cross-sectional study of alexithymia in patients with relapse remitting form of multiple sclerosis - J Stojanov (Journal of Postgraduate Medicine, 2020)
Background: Alexithymia is one's incapacity to identify, comprehend, and describe emotions. There is almost no literature data about the levels of alexithymia among patients with relapse remitting type of multiple sclerosis. Aim: The objective of the present study was to assess the levels of alexithymia in patients with relapse remitting type of multiple sclerosis in relation to their sociodemographic variables and clinical characteristics of the disease. Methods: This cross-sectional study included 106 consecutively assessed patients with relapse remitting type of multiple sclerosis. In addition to the data regarding disease duration, number of demyelinating relapses, and degree of neurological disability, assessed by the expanded disability scale score (EDSS), we used Toronto alexithymia scale (TAS), fatigue severity scale (FSS) and, Hamilton scale for the assessment of anxiety and depression and sociodemographic questionnaire. Results: Study included 74 female and 32 male patients, with a median age of 44 years, median disease duration 90 months, and median EDSS 4. About 29.55% of patients had alexithymia and borderline alexithymia was observed in 31.15% patients. Alexithymia correlated with anxiety and depression (P < 0.01) on all TAS subscales. Higher levels of neurological disability based on EDSS, severe fatigue based on FSS scores, and severe relapse remitting type of multiple sclerosis with more relapses and longer disease duration correlated with alexithymia (P < 0.01), depression (P < 0.01), and anxiety (P < 0.01). Higher rates of alexithymia were noticed in older, unemployed, single patients, and those having fewer children. Conclusions: Alexithymia was found in a relatively high percentage in patients with relapse remitting type of multiple sclerosis.